Mexican Government actions to face the SARS-CoV2 virus health emergency - González Graciano, Augusto Federico; Graciano Casas, Lucía (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Analyze through the Law, the news social incidents working conditions and actions, in contrast to the legal elements in labor matters that are required forthe newhealth reality emergency due to the disease caused by the caused by the SARS-CoV2 Virus.